Dampak Komisaris Independen, Ukuran Perusahaan, dan Return On Assets Terhadap Nilai Perusahaan Sub Sektor Produk Rumah Tangga Tidak Tahan Lama Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Raihansyah, Muhammad; Sutrisno, Bambang (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research is entitled "The Impact of Independent Commissioners, Company Size, and Return on Assets on the Company Value of Non-Durable Household Products Sub-Sectors Listed on the Indonesia Stock Exchange in 2019-2023". The aim of this research is to determine and analyze the impact of independent commissioners, company size, and return on assets on company value. This research design is associative with an associative type. This study uses secondary data. The population of this study is the household products sub-sector listed on the Indonesia Stock Exchange in 2023, totaling 11 companies. Sampling using purposive sampling and 6 companies were obtained as research samples. The method used is panel data analysis using Eviews 12 SV. Determination of the model with the chow test, hausman test, lagrange multiplier test, classical assumption test and using the regression equation, coefficient of determination and hypothesis test. The research results show that the council is ndependent commissioners have a positive and significant effect on company value, company size has a negative and insignificant effect on company value, company size has a negative and insignificant effect on company value, and return on assets has a positive and insignificant effect on company value.